1984
DOI: 10.1002/pen.760240209
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and mechanical behavior of the UHMWPE/MDPE mixtures

Abstract: An attempt was made to melt incorporate ultra high molecular weight polyethylene, UHMWPE, into medium density polyethylene, MDPE. The behavior of the mixtures, containing up to 6 wt percent of UHMWPE, was examined using mechanical and rheological testing. The mechanical test results were found to contain large experimental errors, which makes interpretation very difficult. On the other hand, melt rheology studies, using dynamic and extensional deformations, gave direct insight into the extent and effect of ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…A similar result was reported in a previous report. 9 Dumoulin et al 9 studied polymer blends of medium-density polyethylene (MDPE) and UHMW-PE at the blend ratio of 98 : 2. Optical observation showed that UHMW-PE was dispersed as particles with 10 -50 m diameter.…”
Section: Strain-rate-independent Linear Elongational Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result was reported in a previous report. 9 Dumoulin et al 9 studied polymer blends of medium-density polyethylene (MDPE) and UHMW-PE at the blend ratio of 98 : 2. Optical observation showed that UHMW-PE was dispersed as particles with 10 -50 m diameter.…”
Section: Strain-rate-independent Linear Elongational Viscositymentioning
confidence: 99%
“…However, it was reported by Dumoulin et al that incorporation of the UHMW polymer into the matrix polymer to make a homogeneous phase with melt compounding had failed. 9 Thus, a different sample preparation method, in the following three steps, was tried: solution blend, cast film, and hot press. Poly(methyl methacrylate) (PMMA) and poly-(acrylonitrile-co-styrene) (AS, 30 wt % of AN) from Asahi Chemical Industry Co., Ltd. were used.…”
Section: Experimental Preparation Of Samplesmentioning
confidence: 99%
“…[1][2][3][4] Furthermore, its sensitivity to melt shearing, as reflected in the early appearance of melt fracture and chain scission, demands less conventional and low-shear processes, such as compaction and sintering, compression molding, or ram extrusion. An additional possibility of exploiting the valuable properties of this material is by blending it with another polymer, either by solvent blending [5][6][7] or melt mixing, 6,7 as in the present study. The effects of high-energy radiation on polyethylene are of considerable scientific and commercial importance, and have been studied in some detail.…”
Section: Introductionmentioning
confidence: 96%
“…This behavior was also reported by Min et al, 16 where they observed that addition of HDPE to PS leads to reduced elongation at break during extensional viscosity measurements of blends leading to unstable drawing. The phenomenon of strain hardening in polymers 22,23 is critical to stable filament drawing operations since strain-hardened materials exhibit a strong resistance against fast stretching of polymer melts, which in turn imparts draw rate stability. Thus, when neat HDPE was spun, the molten strand showed severe necking instabilities after emerging from the die and subsequent rupture of filaments occurred.…”
Section: Melt-drawing Of Blendsmentioning
confidence: 99%